SARS-CoV-2 infection induces sustained humoral immune responses in convalescent patients following symptomatic COVID-19 - Wu, Jun; Liang, Boyun; Chen, Cunrong; Wang, Hua; Fang, Yaohui; Shen, Shu; Yang, Xiaoli; Wang, Baoju; Chen, Liangkai; Chen, Qi; Wu, Yang; Liu, Jia; et al. (Nature communications, 2021)
Long-term antibody responses and neutralizing activities in response to SARS-CoV-2 infection are not yet clear. Here we quantify immunoglobulin M (IgM) and G (IgG) antibodies recognizing the SARS-CoV-2 receptor-binding domain (RBD) of the spike (S) or the nucleocapsid (N) protein, and neutralizing antibodies during a period of 6 months from COVID-19 disease onset in 349 symptomatic COVID-19 patients who were among the first be infected world-wide. The positivity rate and magnitude of IgM-S and IgG-N responses increase rapidly. High levels of IgM-S/N and IgG-S/N at 2-3 weeks after disease onset are associated with virus control and IgG-S titers correlate closely with the capacity to neutralize SARS-CoV-2. Although specific IgM-S/N become undetectable 12 weeks after disease onset in most patients, IgG-S/N titers have an intermediate contraction phase, but stabilize at relatively high levels over the 6 month observation period. At late time points, the positivity rates for binding and neutralizing SARS-CoV-2-specific antibodies are still >70%. These data indicate sustained humoral immunity in recovered patients who had symptomatic COVID-19, suggesting prolonged immunity. A better understanding of longitudinal changes in antibody responses in COVID-19 patients is needed. Here the authors analyze anti-spike and anti-nucleocapsid antibody responses to Sars-CoV-2 over a course of 6 months in a large cohort of patients with COVID-19, showing that IgM is mostly not detectable after 3 months, whereas IgG responses contract, yet remain at high levels at 6 months.